Reduction in nutritional quality and growing area suitability of common bean under climate change induced drought stress in Africa - Hummel, Marijke; Hallahan, Brendan F.; Brychkova, Galina; Ramírez Villegas, Julián Armando; Guwela, Veronica; Chataika, Bartholomew Y.E.; Curley, Edna; McKeown, Peter C.; Morrison, Liam; Talsma, Elise F.; Beebe, Stephen E.; Jarvis, Andy; et al. (Springer, 2018)
Climate change impacts on food security will involve negative impacts on crop yields, and potentially on the nutritional quality of staple crops. Common bean is the most important grain legume staple crop for human diets and nutrition worldwide. We demonstrate by crop modeling that the majority of current common bean growing areas in southeastern Africa will become unsuitable for bean cultivation by the year 2050. We further demonstrate reductions in yields of available common bean varieties in a field trial that is a climate analogue site for future predicted drought conditions. Little is known regarding the impact of climate change induced abiotic stresses on the nutritional quality of common beans. Our analysis of nutritional and antinutritional compounds reveals that iron levels in common bean grains are reduced under future climate-scenario relevant drought stress conditions. In contrast, the levels of protein, zinc, lead and phytic acid increase in the beans under such drought stress conditions. This indicates that under climate-change induced drought scenarios, future bean servings by 2050 will likely have lower nutritional quality, posing challenges for ongoing climate-proofing of bean production for yields, nutritional quality, human health, and food security.